2017
DOI: 10.1016/j.bcp.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of N -acetyltransferase increases the interactions of isoniazid with endobiotics in mouse liver

Abstract: Acetylation is the major metabolic pathway of isoniazid (INH) mediated by N-acetyltransferases (NATs). Previous reports suggest that slow acetylators have higher risks of INH hepatotoxicity than rapid acetylators, but the detailed mechanisms remain elusive. The current study used Nat1/2(−/−) mice to mimic NAT slow metabolizers and to investigate INH metabolism in the liver. We found that INH acetylation is abolished in the liver of Nat1/2(−/−) mice, suggesting that INH acetylation is fully dependent on NAT1/2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(67 reference statements)
3
1
0
Order By: Relevance
“…3B), which is because deficiency of NAT slows down INH acetylation, leading to INH accumulation in the liver and therefore increasing the interactions between INH and NAD + . The increase of INH-NAD in the liver of Nat1/2(-/-) mice is consistent with our previous finding that NAT deficiency increases the interactions of INH with endobiotics in the liver (Wang et al, 2017).…”
Section: Dose-and Time-dependent Formation Of Inh-nad and Acinh-nad Isupporting
confidence: 92%
See 1 more Smart Citation
“…3B), which is because deficiency of NAT slows down INH acetylation, leading to INH accumulation in the liver and therefore increasing the interactions between INH and NAD + . The increase of INH-NAD in the liver of Nat1/2(-/-) mice is consistent with our previous finding that NAT deficiency increases the interactions of INH with endobiotics in the liver (Wang et al, 2017).…”
Section: Dose-and Time-dependent Formation Of Inh-nad and Acinh-nad Isupporting
confidence: 92%
“…After INH administration, both INH-NAD and AcINH-NAD were quickly formed in the liver, and reached the highest levels at 15 min, and then decreased to undetectable levels after 4 hr ( Fig. 2C and D), which is consistent with the pharmacokinetics of hepatic INH and AcINH (Wang et al, 2017 than INH-NAD by comparing their peak areas ( Fig. 2C and D), although the differences of their ionization efficiencies cannot be ruled out.…”
Section: Dose-and Time-dependent Formation Of Inh-nad and Acinh-nad Isupporting
confidence: 76%
“…INH is metabolized by N-acetyltransferases (Nat1, Nat2) to acetyl hydrazine and finally hydrolyzed to non-toxic diacetyl hydrazine for excretion. The in-duction of INH+RIF leads to the down-regulation of Nat1 and Nat2 expression, which leads to reduced acetylation of INH and production of toxic hydrazine [21,22], which was also observed in this study and reversed by the BER intervention (Figures 3A,B and 7A). Furthermore, due to the overlapping substrate specificity and the unresolved functional significance of the Nat1 and Nat2 allelic variants, caution must be exercised in interpreting the tissue localization of them based on metabolic activity.…”
Section: Discussionsupporting
confidence: 80%
“…Using a high-dose treatment of isoniazid in an animal model, an overdose of isoniazid resulted in the accumulation of oleoyl-I-carnitine and linoleoyl-I-carnitine in the liver, which further led to mitochondrial dysfunction [54]. A recent study used Nat1/2 −/− mice as a genetic model for NAT slow metabolizers revealed increases in interactions of isoniazid with certain endobiotics, including fatty acids and vitamin B6, which may provide novel insights into the mechanisms of isoniazid-induced liver injury [55]. However, more experiments are required to illustrate the role of NAT2 variants in a higher risk of AT-DILI.…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%